History of Mathematics in Mathematics Education – An Overview (mathematica didactica, 2019)
This paper aims to provide an overview of the research on the relations between History of Mathematics and Mathematics Education (what we call the “HPM domain”1) with emphasis on some of the more recent developments. In section 1 we outline the aim and structure of the paper, while in section 2 we explain the rationale underlying this domain (what we call the “HPM perspective”). Section 3 and the appendix provide a brief historical account of the development of the HPM domain with reference to the main international activities in its context and their outcomes and special reference to these activities in Germany. In the main part of the paper (section 4) we formulate the key issues addressed in this domain and attempt to present the work done structured by these issues. Finally, in section 5 we comment briefly on the central issues to be further pursued in research.